Relation between large amplitude oscillatory shear analysis and bubble forming properties of chewing gum - Yildirim-Mavis, Cigdem; Ozmen, Duygu; Akdeniz, Esra; Palabiyik, Ibrahim; Toker, Omer Said (ELSEVIER SCI LTD, 2023)
In this study, Tack analysis was employed for supporting LAOS parameters (e3/e1 and v3/v1) to characterize the properties of four types (633, 680, 213, 810) of gum base. For 633, 680 and 213, an increase in the elastic stress component (curvature of central curved lines: d2 sigma MODIFIER LETTER PRIME/d2 gamma > 0) of the total stress was observed at the 14.8% strain point, suggesting that the elastic response played the dominant role and they exhibited intracycle strainstiffening behaviour. When the rate of deformation increases towards the nonlinear region, the first sample to lose its elliptical shape is 213. Max. Normal force value (N) of 213 obtained from Tack analyses was the highest. This information also leads conclusion of the bubbling capability of the gum bases which were reported as extensibility properties (213 < 633<680 < 810) declared by the chewing gum manufacturer. Tack analysis results, and LAOS parameters can provide important information about bubble-forming properties of the gum.
Keywords: Chewing gum; Gum base; Non-linear rheology; LAOS; Tack analysis; LAOS BEHAVIOR; GEOMETRICAL INTERPRETATION; PARAMETERS; Engineering; Food Science & Technology